Testosterone May Hold Therapeutic Promise for the Treatment ofIschemic Stroke in Aging: A Closer Look at Laboratory Findings - Fereshteh Farajdokht; Mehdi Farhoudi; Alireza Majdi; Masumeh Zamanlu; Saeed Sadigh-Eteghad; Shabnam Vahedi; Javad Mahmoudi (Tabriz University of Medical Sciences, 2019)
Male sex is more prone to cerebrovascular disorders, yet the exact role of androgens in cerebralischemia remains unclear. Here we reviewed current understanding of testosterone (TES)neuroprotective activity against ischemic stroke and mechanisms underlying these effects inaging. TES may exert a neuroprotective effect in aging through pathways including inhibition ofoxidant molecules production, enhancing the enzymatic antioxidant capacity of the brain andmodulation of apoptotic cell death. Given this, a better understanding of the neuroprotectiveroles of TES may propose an effective therapeutic strategy to improve the quality of life anddecrease androgen-related cerebrovascular problems in the aging men.